Application of Guided Imagination to Reduce Pain in Post Open Reduction Fracture Patients Internal Fixation (ORIF) - Karunia, Zty; Yudha, Raden Rama Widya Kartika; Margaretha, Sumarti Endah Purnamaningsih Maria (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
A fracture is a disruption of the normal continuity of the bone and surrounding soft tissue. This fracture can cause pain which is a subjective sensation and emotional experience of the sufferer. One non-pharmacological therapy to reduce pain is to use guided imagery. In 2018, the incidence of bone fractures in D.I.Yogyakarta was 64.5%. Objective describes the application of guided imagery to reduce pain in post-operative fracture patients in Ward Cendana 2 Dr. Sardjito Hospital. Methods The descriptive method used is a case study to obtain an overview by observing and analyzing accurate data so that it is easy to understand. Result After applying guided imagery to post-operative fracture patients at Dr. Sardjito General Hospital with a frequency of 2 times a day for 3 days, the pain results decreased from scale 6 (moderate pain) to scale 1 (mild pain). Conclusion Based on the results of a case study conducted at Dr. Sardjito Hospital, Yogyakarta for 3 days with a duration of 10-15 minutes, it can be concluded that guided imagery can reduce pain in post-operative fracture patients.